Development of a Building Structural System Using An IsoTruss® Grid. (2017) - Kim, Tae-Heon; Lee, Han-Ul; Kim, Young-Chan
Abstract: Conventional frame building methods use orthogonal placement of beams and columns at the exterior of the building. Modern buildings with unconventional structural systems, such as diagrid systems, are becoming popular. In this study, the IsoTruss ® grid is applied to a building structural system and its behavior is compared with that of a diagrid system. Exterior columns, placed vertically and obliquely, are connected in a zigzag pattern over the height of the building, making a unique façade, and are instrumental in reducing wind loads. The results of our analysis show that the structural performance of the proposed system is comparable to that of the diagrid system.